Update on the treatment of post-menopausal osteoporosis. - Cole, Z; Dennison, E; Cooper, C (2008)
BACKGROUND: Osteoporosis has a huge impact on public health, through the increased morbidity, mortality and economic costs associated with resultant fractures. The goal is to evaluate and identify those that are at risk of osteoporotic fracture in order to start preventative and therapeutic measures to reduce their risk of fracture. SOURCES OF DATA: This article reviews the data from randomized controlled trials for the current therapeutic agents available in the UK. It also reviews new trial data for promising osteoporosis therapies, in particular Denosumab, a monoclonal antibody against RANK ligand. AREAS OF AGREEMENT: Bisphosphonates are the current recommended first-line treatments for patients with osteoporosis. AREAS OF CONTROVERSY/GROWING POINTS: There are a number of patients where bisphosphonates are contraindicated. Under these circumstances, it is important that clinicians have access to alternative treatments. The long-awaited National Institute for Health and Clinical Excellence (NICE) technology appraisals for both primary and secondary prevention and the clinical guidelines will clarify this. Treatment decisions should be based on risk factors and pharmaceutical intervention given to those with the highest risks. AREAS TIMELY FOR DEVELOPING RESEARCH: Future studies are required to look at these agents in combination to see whether anti-fracture efficacy can be improved.